(untitled) (Bangladesh Pharmaceutical Journal, 2022)
Hospital pharmacy and graduate pharmacists are part and parcel of a proper healthcare system. This study aims to assess Bangladesh’s current hospital pharmacy practice and drug management system. A face-to-face interview-based survey was designed, and 15 hospitals of Khulna Division of Bangladesh were subjected to evaluation by a close-ended questionnaire containing 17 questions regarding hospital pharmacy practice and drug management system. Among 15 hospitals, 67% had hospital pharmacy services, whereas 47% had “C” grade pharmacists, and 53% of hospitals had no narcotic drug locker. Surprisingly, 87% of hospitals had no PTC (pharmacy and therapeutic committee), and 40% had no control over drug abuse. Besides, only 6.67% of hospitals had graduate pharmacists (A grade pharmacists), and 33% had no pharmacists. Furthermore, 67% of hospitals provided drug-using information, and 60% of hospitals provided no dosing information to their patients. Moreover, 40% did not maintain the record for expired products and had no “not for sale” tag for expired or damaged medicines. The current study findings suggest that the respective authorities must revisit the current healthcare system and take immediate initiatives to appoint graduate pharmacists in every hospital to improve the medical service with a proper drug management system. Bangladesh Pharmaceutical Journal 25(1): 44-53, 2022 (January)